Pendidikan Multikultural Di Perguruan Tinggi - Lilik Andaryuni (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2014)
The background of this study is the existence of various etnics, tribes, and culture in Indonesia. The diversity becomes social power to develop the nation. The conflicts, happened in some places in Indonesia, are the pictures how diversity could create violenceand and lost. That is why, the multiculturalism education is important to be developed. STAIN Samarinda, which is the only one Islamic higher education in Kalimantan Timur, also concerns to this issue. This study shows that the implemetation of multiculturalism education at STAIN Samarinda running well. STAIN Samarinda implements the multiculturalism education by: (a) making MoU with some social institutions, social groups, banks, and others. (b) considering gender; there is no gender discrimination at STAIN Samarinda. (c) making students’ center activities, such as: BEM, UKM band, UKM teater iqra’, KSR, boy-scouts, and others. In terms of the strategy in enriching multiculturalism values, STAIN Samarinda put this subject into the process of learning at STAIN Samarinda.